Redefining the anthropomorphic animal in animation - Gillian E. Bliss (2017)
The use of anthropomorphic animal characters is pervasive in animation, but there has been little examination of how and why these are created, and how a viewing audience understands them. This Practice-based PhD examines how a re-defining of anthropomorphic and zoomorphic representation might bring a new impetus to the use of animal imagery within contemporary animation practice. An initial stage of research was to define the term anthropomorphism both as a visual language within animation practice and in the wider contexts of scientific and philosophical discourse. Social and psychological aspects are discussed, recognising this form of hybrid representation throughout the development of human culture. Links with Human Animal Studies disciplines raised the question of relating anthropomorphism to negative aspects of anthropocentrism and this led to a second stage of the research that explores ways of working with anthropomorphism that do not promote an anthropocentric bias. This is firstly achieved through the devising of a new theoretical approach to character analysis that is based on the recognition of perceptual aesthetic and sensual animal qualities in human-led , animal-led and design-led anthropomorphic characters, rather than a reliance on conceptual symbolic referencing of human experiences, goals, and narratives. Moving into the practice and influence from historical animation work provides impetus for a move away from character and narrative based work. Experimental animation techniques are used to create rhythms and patterns of abstracted animal and human imagery. This new work is based on contemporary ecological ideas that discuss relationships between humans and animals as interconnected species, thus providing a second way of lessening of anthropocentric bias in the subject matter. Having a starting point of aesthetic and sensual responses to actual experiences with animals is an important factor and live action film is re-animated to create digitally manipulated rhythms of colour, texture, movement and sound. The practical research outcomes are animation samples that evidence the coming together of experimental digital techniques and contemporary ecological subject matter. An action research model was devised for the research to enable the integration of theory and practice, and reflection on theory and practice to have an important influence on the practical outcomes. The approach taken was dependent on experience as a creative practitioner and as a teacher helping others to develop a sustainable creative practice, in allowing an open and intuitive discovery of ideas from both theoretical and practical explorations to create a flow through the research. The combination of theoretical and practical research undertaken provides an impetus towards the creation of future animation work using an anthropomorphic visual language redefined as zooanthropomorphic animation . The submission includes outcomes of a written thesis and links to practical animation work.